Intercultural Communication in the Implementation of Multicultural Education Performed by Islamic Religion Education Teachers of Senior High Schools - Inayah, Sitti Syahar; Raisuddin, Muhammad (IAIN Samarinda, 2019)
The occurrence of intercultural communication in multicultural education is indicated by the sense of equality in the education process, regardless of ethnicity, social class and the gender of the students. The dynamics of Islamic Religion Education, which was executed through an approach so-called ‘multicultural education’, combines traditions and learning process. Thus, the teachers were supposed to be the communicators who underline some particular factors such as readiness and empathy. The aim of this paper, therefore, is to describe the dynamics of intercultural communication in the settings of multicultural education performed by High School’s Islamic Religion Education (PAI) teachers in Makassar. This qualitative study found that teacher’s readiness was changing every time they taught another class with another academic major. A practical approach was the one preferred by the students of all kinds of academic majors, unlike the discussion and lecture approach. The other finding of this study was that teachers were more likely to show cognitive empathy rather than affective empathy.Keywords: Intercultural Communication, Multicultural Education, Islamic Religion Education